Multifrequency Pulsed EPR and the Characterization of Molecular Dynamics - Eaton, Sandra S. (Methods Enzymol, 2015)
In fluid solution motion-dependent processes dominate electron spin lattice relaxation for nitroxides and semiquinones at frequencies between 250 MHz and 34 GHz. For triarylmethyl radicals motion-dependent processes dominate spin lattice relaxation at frequencies below about 3 GHz. The frequency dependence of relaxation provides invaluable information about dynamic processes occurring with characteristic times on the order of the electron Zeeman frequency. Relaxation mechanisms, methods of measuring spin-lattice relaxation, and motional processes for nitroxide, semiquinone, and triarylmethyl radicals are discussed.